Harmful impact of radioactive iodine (I131) therapy on hematological parameters in thyroid disease patients - Shahid, Imran; Mubeen, Hira; Rakha, Allah (International Journal of Pathology, 2025)
Radioactive Iodine-131 is used to treat benign and malignant hyperthyroid patients. It is concentrated in thyroid tissue when taken orally. It destroys thyrocytes by omitting beta rays and also by producing reactive oxygen species (ROS). As it circulates through the blood stream, I131 causes direct harm to blood cells through beta radiation and indirect harm by producing free radicals. The study aims to investigate damaging effects of I131 on hematological parameters in patients with thyroid diseases. Methods: A total of 100 hyperthyroid patients were recruited and split into four groups: male low-dose, female low-dose, male high-dose and female high-dose groups depending on their I131 dosage. Health professionals at PINUM Cancer Hospital Faisalabad administered I131, provided by the Pakistan Atomic Energy Centre Islamabad, to the patients. Hematological markers were evaluated prior as well as after I131 therapy. Results: Following I131 therapy, total leukocyte count remained stable but the absolute lymphocyte count (ALC), RBCs count and platelets counts declined significantly within two weeks. ALC decreased 41.7%, and platelets dropped by 25% whereas RBCs displayed a reduction of 10%. Gender wises the decline in ALC was same in both genders but in platelets count the decline was higher in males while the decline in RBCs count was higher in females. Neutrophils presented hyper-segmentation of chromatin while cytoplasmic vacuolation and micronuclei formation were seen in lymphocytes. Conclusions: Radioiodine therapy has the damaging effects on blood cells and causes a significant decline in lymphocytes, RBC and platelets counts. I131 also exhibited genotoxic effect on neutrophils and lymphocytes.